Exploration of analgesia with tramadol in the coxsackievirus B3 myocarditis mouse model - Pinkert, Sandra; Kespohl, Meike; Kelm, Nicolas; Kaya, Ziya; Heuser, Arnd; Klingel, Karin; Beling, Antje (Viruses, 2021)
Infection of mice with Coxsackievirus B3 (CVB3) triggers inflammation of the heart and this mouse model is commonly used to investigate underlying mechanisms and therapeutic aspects for viral myocarditis. Virus-triggered cytotoxicity and the activity of infiltrating immune cells contribute to cardiac tissue injury. In addition to cardiac manifestation, CVB3 causes cell death and inflammation in the pancreas. The resulting pancreatitis represents a severe burden and under such experimental conditions, analgesics may be supportive to improve the animals’ well-being. Notably, several known mechanisms exist by which analgesics can interfere with the immune system and thereby compromise the feasibility of the model. We set up a study aiming to improve animal welfare while ensuring model integrity and investigated how tramadol, an opioid, affects virus-induced pathogenicity and immune response in the heart. Tramadol was administered seven days prior to a CVB3 infection in C57BL/6 mice and treatment was continued until the day of analysis. Tramadol had no effect on the virus titer or viral pathogenicity in the heart tissue and the inflammatory response, a hallmark of myocardial injury, was maintained. Our results show that tramadol exerts no disruptive effects on the CVB3 myocarditis mouse model and, therefore, the demonstrated protocol should be considered as a general analgesic strategy for CVB3 infection.